Credit Constraints on Small Business: Theory Versus Evidence - Cressy, Robert (Senate Hall, 2003)
We describe the prevailing theories of credit constraints, empirical tests of the theories and their policy implications. Theories and empirical tests are then evaluated in the context of small businesses and the likelihood of encountering credit constraints in practice is assessed. Private and public sector responses to perceived credit constraints are then evaluated on both theoretical and empirical grounds and broad conclusions reached about the relevance and effectiveness of policy initiatives. The paper is a written-up version of a lecture that I deliver as part of a course taught to second year students on the BSc degrees at Cass Business School, London. The only prerequisite for the course is that the students should have taken Elementary (Micro and Macro) economics.
Keywords: credit constraints|small business|policy response